Biological community structure in Krueng Sarah River, Aceh Besar District. Issue 1 (February 2021) - Octavina, C; Razi, N M; Agustiar, M; Sakinah, R; Fazillah, M R; Sahidin, A
Abstract: This study aims to determine the biological community structure (plankton and macrozoobenthos) in the river from 2017 to 2019. This research method is purposive sampling. The results showed that there were five species of macrozoobenthos, namely Neritrodyas (2017), Polinices hepaticus, Telebra gulata, and Telebralia sulcate (2018), and Tronchus concave (2019). Overall the abundance was high and the same in the three stations. The diversity index (H') is classified as moderate, while the similarity (E) and dominance (D) are classified as high. Plankton data shows that 15 species of biota were found, namely Rhizoselenia stolterfazhii, Hemialus sp. (2017), Civutum hinnalinclla, Bulduehatae sp., Planctotturnix sp., Canccella sp., Cospidothrea sp., Rhizosolenia sp., and Alana bullata (2018) Isothrix spopsi ., Fragila sp., Cylindrusperm raciborska, Cuspidothrix sp., Flagiloria sp., and Cosmarium sp. (2019). Overall, the abundance of plankton is still high. The plankton diversity index is high each year, while the similarity and dominance are low. The water quality data of Krueng Sarah shows that it is still within the tolerance limits for macrozoobenthos and plankton. Therefore, the overall structure of the biological community in Krueng Sarah is still classified as suitable for natural balance.